Maltrato infantil y neurociencias - Amaro Hurtado, Fiorella (2020)
Child abuse is addressed, from the perspective of neuroscience, considering a pressing need to know the modifications and neurobiological effects of abuse in a stage of life that is in a process and critical period of neurodevelopment, constituting a stage of special vulnerability to the various stressful situations and adverse experiences that generate an impact on the cognitive, emotional and social development of the human being. After defining the treated topic and its epidemiological implications, postnatal development and the consequences of child maltreatment are exposed on the development of the central nervous system, reviewing the state of the art in relation to the findings observed in structural and functional neuroimaging of the brain. This review explores the contributions of epigenetics as a relevant modulating variable of child maltreatment in the outcome of internalized and externalized disorders in children and adolescents, finally providing future perspectives.